El uso combinado de hidrocloruro de ketamina (khcl) e hidrocloruro de xilacina (xhcl) para inmovilizar coyotes silvestres (Canis latrans) - Servín, Jorge; Huxley, Carmen; Vences, Martha (Instituto de Ecología, A.C., 1989)
A mixture of two drugs: a myorelaxing sedative xilazine (xhcl) and a narcotic-cataleptic, ketamine (khcl) to inmobilize wild canids is reported in this communication. Coyotes were intramuscularly hand-injected. Dosages used (ketamine 0.5 ml; xilazine 1.1 ml) kept the animals enough time to handle them, mean 95 minutes to record standard measurements, weight and sex. A radio-collared was attached to them. Death, cardiac arhytmy, stop breathing, vomit or bleeding has never been seen while we treated them under this drugs mixture. It has been an accesible and safe method for animal and its capturer. All the animals has been monitored until now, apparently without physical deficiences. This ketamine-xilazine combination is recommended to wildlife managers.